Optimizing the Role of the Palengaan East Java KSPPS on the Welfare of the Palengaan Pamekasan Community - Hamdy, Mohammad Zainal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Cooperation is a body of law-abiding and family-based endeavors by prioritizing the sense of brotherhood to members as a whole. Cooperation in the midst of society aims to promote the well-being of members in particular and society in general. The problem with the trees that emerged in this research is how does cooperation play a role in the well-being of members? How are the controls faced by NURI KSPPS cooperation in improving the well-being of members? and how is the Strategy used to cooperate in addressing controls in the Enhancement of Members' Peace? This study aims to provide an understanding of the role of cooperation in improving members' well-being.The research used is descriptive qualitative research This research is part of field research and data is collected by looking at what it sees, analyzing data and gathering it. Data collection techniques used are interviews, observations and documentation.The results of the research show that 1) NURI's KSPPS cooperation plays a very important role in the clarification of its members, the form of its well-being: the ease of the service provided, helping to fund child education, health guarantees for officials, and BMN assistance. (3) The strategy or solution is to increase the ability to visit or motivate each branch in its role.